A coursebook on translation - Baker, Mona (London, 2018)
This book includes many parts: equivalence at word level; equivalence above word level; grammatical equivalence; textual equivalence; thematic and information structures,...
Biên dịch môi trường
Keywords: Biên dịch và phiên dịch,Translating and interpreting